2013
DOI: 10.3988/jcn.2013.9.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Multimarker Approach in Discriminating Patients with Symptomatic and Asymptomatic Atherosclerotic Carotid Artery Stenosis

Abstract: Background and PurposezzSeveral circulating biomarkers have been implicated in carotid atherosclerotic plaque rupture and thrombosis; however, their clinical utility remains unknown. The aim of this study was to determine the role of a large biomarker panel in the discrimination of symptomatic (S) vs. asymptomatic (A/S) subjects in a contemporary population with carotid artery stenosis (CS).MethodszzProspective sampling of circulating cytokines and blood lipids was performed in 300 unselected, consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 47 publications
0
43
1
8
Order By: Relevance
“…Despite accumulating evidence showing an increased risk of clinical CVD events to be associated with the Lp-PLA2 level, the association between the Lp-PLA2 level and subclinical atherosclerosis is less established, and the findings of limited cross-sectional and casecontrol studies are inconsistent [7][8][9][10][23][24][25] . In the present analysis, the Lp-PLA2 level was found to be significantly associated with the presence of baseline carotid plaque in men, but not women.…”
Section: Discussionmentioning
confidence: 99%
“…Despite accumulating evidence showing an increased risk of clinical CVD events to be associated with the Lp-PLA2 level, the association between the Lp-PLA2 level and subclinical atherosclerosis is less established, and the findings of limited cross-sectional and casecontrol studies are inconsistent [7][8][9][10][23][24][25] . In the present analysis, the Lp-PLA2 level was found to be significantly associated with the presence of baseline carotid plaque in men, but not women.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Along with others, we also detected no significant differences in adiponectin levels between symptomatic versus asymptomatic subjects with moderate-to high-grade CAS. 46,47 Interestingly, it was recently reported that perivascular adiponectin expression, rather than circulating adiponectin, is significantly associated with symptomatology in patients undergoing CEA. Perivascular adipose tissue surrounding symptomatic carotid plaques expressed 1.9-fold higher levels of adiponectin than asymptomatic plaques.…”
Section: Adiponectin's Vasculoprotective Propertiesmentioning
confidence: 99%
“…4,14,21 For a significant proportion of these patients, a "not-yetsymptomatic" or "at risk of symptomatic transformation" label would be more accurate than the "asymptomatic" label, but the field suffers from lack of effective risk discrimination tools. 19 While the need for revascularization in symptomatic patients is not controversial (albeit the treatment arrives too late to prevent brain damage! ), it is surprising to the vascular community that, in the absence of any reliable evidence, vocal and powerful calls are being made to "stop revascularization in asymptomatic patients" 22 and "just stick to medical therapy."…”
Section: Cs and Stroke Riskmentioning
confidence: 99%